2011
DOI: 10.1080/07347332.2011.534024
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Demographic, and Situational Factors Linked to Distress Associated with Benign Breast Biopsy

Abstract: Few studies have examined the magnitude of distress associated with specific aspects of the benign breast biopsy (BBB) or distress risk factors. Women (n=51) completed questionnaires regarding distress associated with a recent BBB experience. Clinical and demographic risk factors for distress were also examined. All women reported distress associated with BBB; one-third reported it as “very stressful.” Biopsy-specific events were rated most distressing. Younger age, less education, non-surgical biopsy, and abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
(69 reference statements)
2
12
0
Order By: Relevance
“…Future research could use instruments used in research and clinical settings (e.g., National Comprehensive Cancer Network Distress Thermometer) to better inform practice. The majority of baseline surveys were conducted prior to administration of biopsies and cancer diagnoses, which are likely to influence coping strategies and distress (Steffens, Wright, Hester, & Andrykowski, 2011). The authors did not collect data on the history of previous receipt of abnormal results, which may have influenced distress and coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Future research could use instruments used in research and clinical settings (e.g., National Comprehensive Cancer Network Distress Thermometer) to better inform practice. The majority of baseline surveys were conducted prior to administration of biopsies and cancer diagnoses, which are likely to influence coping strategies and distress (Steffens, Wright, Hester, & Andrykowski, 2011). The authors did not collect data on the history of previous receipt of abnormal results, which may have influenced distress and coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Although stereotactic and MR imagingguided biopsies have less comfortable positioning, require breast compression throughout the procedure, and have longer average biopsy procedure times than US-guided procedures, there was no significant association between (26) found that younger women were more distressed not only by the biopsy experience but also by some of the steps leading up to the biopsy, such as awaiting diagnostic mammography after a screening examination with abnormal findings. Using the State Trait Anxiety Inventory, Seckel and Birney (27) found that as women approach the age of 40 years, biopsy-associated stress increased; however, beyond age 40 years the degree of stress decreased with patient age.…”
Section: Breast Imaging: Percutaneous Breast Biopsy: Effects On Shortmentioning
confidence: 43%
“…All the patients that undergo breast biopsy state that they experience biopsy-related stress even though the results are benign. Once the decision for biopsy is made, the procedure being conducted and the time that elapses until the results are received raises the stress levels of patients (27). Furthermore, the anxiety that patients experience due to biopsy are much higher than the anxiety that develops after the request for an additional study or due to follow-up mammography examinations (28,29).…”
Section: Discussionmentioning
confidence: 99%